Pengaruh Produk Green Marketing Dan Brand Image Terhadap Keputusan Pembelian (Survei pada Konsumen Starbucks HZ Tasikmalaya) - Alda Nita Nur Agustin; Budhi Wahyu Fitriadi; Depy Muhamad Pauzy (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2025)
This study aims to analyze and determine the effect of Green Marketing and Brand Image on Purchasing Decisions at Starbucks HZ Tasikmalaya both simultaneously and partially. This study uses a quantitative research method with a survey approach. The sampling technique used is simple random sampling and the sample taken is 100 respondents. The analysis tool used in this study is multiple linear regression using SPSS version 26. The results of the study indicate that Green Marketing and Brand Image simultaneously have a significant effect on Purchasing Decisions at Starbucks HZ Tasikmalaya. Green Marketing partially has a significant effect on Purchasing Decisions at Starbucks HZ Tasikmalaya. Brand Image partially has a significant effect on Purchasing Decisions at Starbucks HZ Tasikmalaya.